SISTEM INFORMASI ADMINISTRASI PINJAMAN (KREDIT) PADA CREDO UNION MODIFIKASI (CUM) BERBASIS WEB - Victor Marudut Mulia Siregar; Erikson Damanik; Mega Romauly Tampubolon; Eve Ida Malau; Eka Pratiwi Septania Parapat; Debora Silvia Hutagalung (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2021)
Modified Union credo is a cooperative-type business entity owned by a group of people in a unifying bond, which agrees to invest their money (shares) so as to create joint capital with decent business results and for productive and welfare purposes. The role of cooperatives is very important in Indonesia, because cooperatives can increase the economic growth of Indonesian society. The loan administration information system (credit) at CUM Caritas HKBP Pematangsiantar is not yet effective, because it still uses a manual system so that data is easily lost and difficult to find, and the preparation of reports takes a long time. The purpose of this study is to build a system that makes it easier for staff to process data for CUM Caritas HKBP members and improve staff performance to be more efficient and minimize errors in data processing, especially in the loan administration (credit) section of CUM Caritas HKBP. In this research, in the process of collecting data, the researcher used the method of observation, interviews and literature study and the method of system development to be used was the Prototype method. The information system to be designed will be in the form of a web and use the MySQL database. It is hoped that this research can solve the problem of Loan Administration (Credit) at CUM Caritas HKBP Pematangsiantar.